Comparação entre os processos de rosqueamento interno por usinagem e laminação - Pereira, Igor Cézar (2014)
Internal threading with formed and cut taps are extremely widespread manufacturing processes within both national and global industry. However, research are still few, being most part of the knowledge mastered and disseminated by tool manufacturers. Yet even the knowledge acquired by the manufacturers over time is still limited and due to the industrial secrets they protect, the most relevant informationare not forwarded. The aim of this paper is to better understand each process and compare their advantages and disadvantages within equal conditions, in order to understand in which situations each process can be advantageous or not. For this assessment, the two main input conditions that were varied in both processes were the workpiece material and the cutting speed. Internal threading, unlike processes such as turning and milling, has a few restrictions and difficulties regarding the alteration of cutting conditions. From these input conditions, the evaluated output parameters were torque, thrust force, microhardness of the screw threads and load break of the threads, in tensile test. Other additional tests were conducted in order to better comprehend the characteristics of the internal threading processes, such as the threaded thickness and length variation, pitch alteration, tool coating variation and a thread by thread torque assessment. One of the found results was that the load break of M10x15 formed and cut threads were statistically the same, yet there was a tendency pointing that the cut thread holds greater tensile stress than the formed screws.